The FARSEEING real-world fall repository: a large-scale collaborative database to collect and share sensor signals from real-world falls - Klenk, Jochen; Schwickert, Lars; Palmerini, Luca; Mellone, Sabato; Bourke, Alan; Ihlen, Espen A. F.; Kerse, Ngaire; Hauer, Klaus; Pijnappels, Mirjam; Synofzik, Matthis; Srulijes, Karin; Maetzler, Walter; et al. (European review of aging and physical activity, 2016)
Real-world fall events objectively measured by body-worn sensors can improve the understanding of fall events in older people. However, these events are rare and hence challenging to capture. Therefore, the FARSEEING (FAll Repository for the design of Smart and sElf-adaptive Environments prolonging Independent livinG) consortium and associated partners started to build up a meta-database of real-world falls.
Gesehen am 13.05.2020